Variation in plant-animal interactions along an elevational gradient of moist forest in a semiarid area of Brazil - Diogo, Ivan Jeferson Sampaio (2016)
Pollination and dispersal are critical ecological processes that directly affect the reproductive success of plants and are important for understanding the structure of plant communities. We compiled data on pollination and dispersal syndromes of 406 plant species distributed among different elevations in Área de Proteção Ambiental da Serra de Baturité (APASB) in northeastern Brazil. We aim to determine how the dispersal and pollination of the flora in the mountainous rainforest of APASB are affected by climate, relief and growth form. We hypothesized that plant community is comprised of different ecological groups based on biotic and abiotic syndromes. Melittophily was the most common (57%) pollination syndrome followed by non-specialized and ornithophily (7%). We found that 64% of species exhibited zoochory, 19% exhibited anemochory and 17% exhibited autochory. Pollination syndromes differed significantly only between types of growth form. Dispersal syndromes differed between topology, growth form and elevation. Six ecological groups were formed based on the interaction between dispersal-pollination and growth form, with predominantly zoochory in woody and anemochory in non-woody plants. Water availability may be the principal factor responsible for variation among dispersal syndromes. The proportion of ruderal species in the non-woody component explains the differences in syndromes between growth forms.